2019
DOI: 10.1002/pca.2861
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and anti‐inflammatory properties of Scurrula ferruginea (Jack) Danser parasitising on three different host plants elucidated by NMR‐based metabolomics

Abstract: Introduction Scurrula ferruginea (Jack) Danser is a hemi‐parasitic shrub that is widely used as a traditional herbal medicine. Objectives To elucidate the anti‐inflammatory activity of S. ferruginea parasitising on three different hosts of Vitex negundo L., Micromelum minutum (G. Forst.) Wight & Arn. and Tecoma stans (L.) Juss ex HBK., as well as, to determine the metabolite differences related to their anti‐inflammatory properties. Materials and Methods Two plant parts of S. ferruginea, stems and leaves, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Watermelon water extract was prepared using the ultrasonication method [ 40 , 41 ]. Powdered biomass (10 g each) was weighed and dissolved in 200 mL Millipore water.…”
Section: Methodsmentioning
confidence: 99%
“…Watermelon water extract was prepared using the ultrasonication method [ 40 , 41 ]. Powdered biomass (10 g each) was weighed and dissolved in 200 mL Millipore water.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, parasitic-host interactions influence the metabolites composition, and biological activities too. Several studies have reported divergences in the composition, quantity, and biological activity of the parasitic plant extracts, when the same parasitic species have been collected from different hosts (Bais & Kakkar, 2013;Fozia et al, 2013;Yusuf et al, 2013b;Bais et al, 2014;Ogunmefun et al, 2015;Furuhashi et al, 2016;Hong et al, 2019). Which might be potential resources of antioxidant and antibacterial activities, according to Abbes et al (2014).…”
Section: )mentioning
confidence: 99%
“…Hence the influence of the host in specific function as herbal medicine cannot be a negligible factor. The host species significantly affect the chemical constituents and biological activities of S. ferruginea [3][4][5]. The common host plants of the mistletoe of S. ferruginea are Tabebuia pallida and Lagerstroemia speciosa [6].…”
Section: ■ Introductionmentioning
confidence: 99%
“…As far as our literature studies, only one exhibited the isolated compounds from the S. ferruginea plant: three flavonols, such as quercitrin, quercetin, and 4"-O-acetylquercitrin from an unspecified host [12]. Another literature reported the chemical constituents of the crude extract based on the principal component analysis (PCA) method from 1 H-NMR data resulting in some identified compounds, such as quercitrin, 4"-O-acetylquercitrin, catechin, alanine, threonine, valine, leucine, isoleucine, histidine, formic acid, malic acid, succinic acid, citric acid, fumaric acid, acetic acid, gallic acid, chlorogenic acid, and choline [5].…”
Section: ■ Introductionmentioning
confidence: 99%